The embodied dynamics of perceptual causality: a slippery slope? - Amorim, Michel-Ange; Siegler, Isabelle A.; Baurès, Robin; Oliveira, Armando M. (Frontiers in Psychology, 2015)
In Michotte’s launching displays, while the launcher (object A) seems to move autonomously, the target (object B) seems to be displaced passively. However, the impression of A actively launching B does not persist beyond a certain distance identified as the “radius of action” of A over B. If the target keeps moving beyond the radius of action, it loses its passivity and seems to move autonomously. Here, we manipulated implicit friction by drawing (or not) a surface onto which A and B are travelling, and by varying the inclination of this surface in screen- and earth-centered reference frames. Among 72 participants (n=52 in Expt 1; n=20 in Expt 2), we show that both physical embodiment of the event (looking straight ahead at a screen displaying the event on a vertical plane vs. looking downwards at the event displayed on a horizontal plane) and contextual information (objects moving along a depicted surface or in isolation) affect interpretation of the event and modulate the radius of action of the launcher. Using classical mechanics equations, we show that representational consistency of friction from radius of action responses emphasizes the embodied nature of frictional force in our cognitive architecture.